2023
DOI: 10.3390/economies11020062
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Crime Rates, Poverty, and Income Inequality: A Case Study of Indonesia

Abstract: This study examines whether income inequality and poverty are determinants of crime rates across 34 provinces in Indonesia. Three indicators of income inequality and four poverty measures are tested to examine whether the dimension and degree of unequal welfare distribution are linked to crime occurrences. We use panel data from 2010 to 2019 with the Generalized Method of Moments (GMM) approach. The findings indicate that higher income levels and wider income inequality are associated with higher crime rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 80 publications
(133 reference statements)
2
14
0
2
Order By: Relevance
“…Studies such as Sugiharti et al (2023), Xue and Zhong (2019), and Ukpere and Slabber (2016) found that unemployment increases poverty, while Xue and Zhong (2019) found that unemployment is a significant cause of urban poverty in China. Vijayakumar (2013) examined the relationship among developing countries' poverty, economic growth, employment and dependency ratio.…”
Section: Unemployment and Poverty Nexusmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies such as Sugiharti et al (2023), Xue and Zhong (2019), and Ukpere and Slabber (2016) found that unemployment increases poverty, while Xue and Zhong (2019) found that unemployment is a significant cause of urban poverty in China. Vijayakumar (2013) examined the relationship among developing countries' poverty, economic growth, employment and dependency ratio.…”
Section: Unemployment and Poverty Nexusmentioning
confidence: 99%
“…Source: World Development Indicator (WDI, 2021). (Pandey et al, 2022;Sugiharti et al, 2023;Ukpere & Slabber, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This metric is not merely an academic construct but has profound implications for societal well-being. It is closely correlated with elevated poverty rates [ 14 ], and its fluctuations can serve as indicators of systemic issues such as restricted upward mobility, entrenched poverty, and burgeoning socio-economic instability. Consequently, the Gini coefficient is an indispensable tool for policymakers, researchers, and international organizations aiming to conduct nuanced evaluations of a country's socio-economic health.…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira (2021), who studied low-income housing in Denmark, stated that crimes like theft increase in urban areas due to the larger population size. Indonesia is similar, with crime rates increasing due to population density that creates a big gap between poor and rich (Sugiharti et al, 2023). Crime has become a key issue for Sabahan locals that greatly impacts their QoL.…”
Section: Introductionmentioning
confidence: 99%